A State of Wonder: The Complete Goldberg Variations - Bach, Johann Sebastian 1685-1750; Gould, Glenn 1932-1982 (Sony, 2002)
The career of the singular and idiosyncratic pianist Glenn Gould is probably best defined by his two recordings of Bach's Goldberg Variations. The first, his major-label debut recorded in 1955, was Gould's breakthrough. A brashly virtuosic performance, it blew the doors off the established notions of playing Bach and catapulted the pianist into superstardom. The second, recorded shortly before his death in 1982, finds a more deliberate Gould giving a poised, introspective reading of the work that brilliantly articulates its emotional intensity. A STATE OF WONDER offers these legendary recordings in remastered versions along with a third disc of outtakes from the 1955 sessions and Gould's carefully scripted final radio "interview." The side-by-side comparison afforded by this excellent package makes for a fascinating listening experience. The two versions are vastly different but both bear the unmistakable stamp of the iconoclastic pianist's characteristic clarity, precision, and dedication. Each could easily be considered a quintessential performance. The remastering is of particular value to the later recording, rescuing it from the unfavorable sound quality of primitive digital technology. This elegantly produced set is a fitting tribute to a remarkable and individualistic artist. It deserves a place on any music lover's shelf.
Keywords: 18th Century (1701-1800); 20th Century (1901-2000); Goldberg Variations; Piano; Canada